ANALYSIS OF THE STORY “SILENCE IN THE MIRROR” BY ARAB WRITER MAHMOUD SHUQAIR (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article presents a scholarly literary analysis of the story “Silence in the Mirror” by the renowned Arab writer Mahmoud Shuqair. The primary aim of the study is to illuminate, through the artistic text, the factors affecting the psychological state of people living under conditions of war and siege. The moods of silence, anxiety, hope, and helplessness depicted in the story are masterfully conveyed by the author through symbols, metaphors, and images drawn from everyday life.